Asparaginase production by human clinical isolates of Vibrio succinogenes. - Radcliffe, C W (1979)
Three human isolates of Vibrio succinogenes produced asparaginase. Apparent Km's were 87,220, and 320 microM. The rate of glutamine hydrolysis was between 2.8 and 3.5% of the rate of asparagine hydrolysis. Asparaginase production was not induced by ammonium ions, and enzyme yields were lower than those obtained with the rumen strain.